2023
DOI: 10.1200/jco.21.02937
|View full text |Cite
|
Sign up to set email alerts
|

Margetuximab Versus Trastuzumab in Patients With Previously Treated HER2-Positive Advanced Breast Cancer (SOPHIA): Final Overall Survival Results From a Randomized Phase 3 Trial

Abstract: Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. Final overall survival (OS) in SOPHIA (ClinicalTrials.gov identifier: NCT02492711 ), a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 13 publications
2
27
0
5
Order By: Relevance
“…26 The SOPHIA study suggested clinical benefit of margetuximab over trastuzumab in patients with ERBB2-positive metastatic breast cancer with CD16A-158F polymorphism. 27 Findings in the present study and the SOPHIA study support the hypothesis of ADCC activity being one of the anticancer mechanisms of trastuzumab and show how the shift in trastuzumab's ADCC activity may affect clinical outcomes. Biologic drugs are produced in living cells through complex multistep processes, and their inherent nature prevents any manufacturer from replicating the exact molecule.…”
Section: Discussionsupporting
confidence: 82%
“…26 The SOPHIA study suggested clinical benefit of margetuximab over trastuzumab in patients with ERBB2-positive metastatic breast cancer with CD16A-158F polymorphism. 27 Findings in the present study and the SOPHIA study support the hypothesis of ADCC activity being one of the anticancer mechanisms of trastuzumab and show how the shift in trastuzumab's ADCC activity may affect clinical outcomes. Biologic drugs are produced in living cells through complex multistep processes, and their inherent nature prevents any manufacturer from replicating the exact molecule.…”
Section: Discussionsupporting
confidence: 82%
“…The hazard ratio for overall survival was 0.95 (95% CI: 0.77 – 1.17). However, for the subcohort who were carriers of the homozygous gene CD16A-158FF, overall survival was better with margetuximab (HR = 0.72; 95% CI: 0.52 – 1.00), while conversely for the rarer genotype CD16-158VV, overall survival results were better with trastuzumab (HR = 1.77 95% CI: 1.01 – 3.12 43 .…”
Section: Biomarkersmentioning
confidence: 96%
“…Die Hazard Ratio für das Gesamtüberleben lag bei 0,95 (95%-KI: 0,77 – 1,17). Jedoch konnte in der Population der homozytogen CD16A-158FF-Träger gezeigt werden, dass das Gesamtüberleben mit Margetuximab besser war (HR = 0,72; 95%-KI: 0,52 – 1,00), während beim selteneren CD16-158VV-Genotyp umgekehrt das Trastuzumab in einem besseren Gesamtüberleben resultierte (HR = 1,77 95%-KI: 1,01 – 3,12) 43 .…”
Section: Biomarkerunclassified
See 2 more Smart Citations